Transcriptomic profiling with vascular tension analyses reveals molecular targets and phenotypes in preeclamptic placental vasculature - Zhang, Eryun; Zhou, Tao; Zheng, Qiutong; Zheng, Xiaomin; Zhang, Yingying; Liu, Bailin; Tang, Jiaqi; Xu, Zhice (Frontiers in Endocrinology, 2024)
The placental vascular systems play important roles in pregnancy hypertension in preeclampsia.Gene profiles between placental whole tissue (containing blood vessels and large amount of other structural components) and pure vascular part should be very different. All previous reports using RNA-seq analysis in the placenta tested its whole tissue or villous part, it is unknown of gene profiles in pure placental blood vessels. This study was first to target this point with RNA-seq in human placenta at transcript level. Isolated placental micro-vessels from normal and preeclamptic pregnancies were used for RNA-seq analysis, RT-qPCR verification, and vascular functional tests.Differential expression analysis identifies a total of 486 significantly changed transcripts.Bioinformatics analysis further confirms that multiple genes are highly related to blood vessel and placental phenotypes. Then, a vascular functional and centric regulatory network was constructed to show the gene-gene interactions and gene-functions associations in placental vessel system.Several hub genes, including ELMO1, YWHAE, and IL6ST, were significantly reduced in the placental vessels of preeclampsia. These results were further verified and confirmed by RT-qPCR.Vascular tension experiments showed that Angiotensin II-mediated vasoconstriction and exogenous NO donors sodium nitroprusside-induced vasodilation were decreased, while phenylephrinemediated vascular responses were unchanged in placental micro-vessels of preeclampsia. The results provide important insights into further understanding pathological process in placental vasculature in preeclampsia, and offer great potentials for further investigations on those molecular targets in human placental vascular system.